Progress Reports on Impedance Spectroscopy : Measurements, Modeling, and Application - Kanoun, Olfa (De Gruyter Oldenbourg, 2016)
Impedance Spectroscopy is a powerful measurement method used in many application fields such as electrochemistry, material science, biology and medicine, semiconductor industry and sensors.This book covers new advances in the field of impedance spectroscopy including fundamentals, methods and applications by contributions from international scientists.